On the international flow of plant genetic resources: Forecasting the impacts of an evolving legal framework on CGIAR genebanks - Gotor, Elisabetta; Caracciolo, Francesco; Pagnani, Tiziana (Bioversity International and the International Center for Tropical Agriculture, 2020)
The aim of this study is to investigate the ex-ante impact of the revision of the Multilateral System of Access and Benefit Sharing (MLS) of plant genetic resources for food and agriculture on CGIAR Centers, and to identify measures to respond to possible negative impacts on CGIAR Centers as recipients and providers of germplasm and associated information under the multilateral system. A process to revise the multilateral system of access and benefit sharing was launched in 2013 and continued until November 2019. The objective was to revise the system to a) increase user-based payments to the Plant Treaty’s benefit sharing fund and b) increase the scope of plant genetic resources included in, and available through, the multilateral system. The negotiations were suspended, at least temporarily, in November 2019. There are ongoing informal discussions between some contracting parties and stakeholders about ways to keep the process of negotiations moving forward, informally for now, and relaunching a formal process in 2021 at the 9th Session of the Governing Body of the Plant Treaty. Meanwhile, one of the same issues that contributed to the suspension of negotiations – disagreement about if and how to require benefit sharing from commercial use of digital sequence information (DSI) -- is being addressed in other intergovernmental fora, including the Convention on Biological Diversity and the FAO Commission on Genetic Resources for Food and Agriculture. Consequently, the proposed research continues to be relevant, and timely, despite the suspension of Plant Treaty negotiations in November.